明清说唱文学中的女扮男装现象 = A study of the phenomenon "women disguised as men" in singing-narratives of the Ming and Qing periods - 洪冰莹 Ang, Ping Ying (2009)
以女扮男装为主题的说唱文学在明清时期的发展达到巅峰。这样一种带有“异端”色彩的文学题材在当时文坛能够引起这么大的关注是一个非常值得探讨的课题，当中就牵涉到了当时的性别观念、社会风气、文化语境等方面的问题。本文旨在从上述不同方面切入，探究这个特殊的文学现象。论文将以晚明作家徐渭《四声猿》中的《雌木兰替父从军》和《女状元辞凰得凤》、清代女剧作家吴藻的《乔影》以及弹词作家陈瑞生的《再生缘》为研究对象，结合当时的社会语境，包括现实生活中的乔装风气和历史传说等方面进行观察，来思考这一题材受到文人青睐的原因。另外，本文也将对几部作品的人物和情节进行归纳，以梳理这类题材的叙事模式。同时，通过对当时社会风气和审美风尚的研究，结合当时普遍盛行的“才女文化”，来观察与梳理文人作家创作的心态，并探讨男女作家在面对相同题材时不同的思考模式和处理方法。During the Ming and Qing dynasties, the theme “women disguised as men” flourished in the Singing-Narratives. The devotion to such a theme is very interesting and warrants investigation. It involves the concept of gender, social custom, cultural context and many other issues during the Ming Qing periods. Four texts under study are Cimulan and Nuzhuangyuan by Xu wei, a literati of the Late Ming Dynasty; Qiaoying by Wu Zao; and Zaishengyuan by Chen Ruisheng, a female writer of the Qing Dynasty. The cultural traits of the society, which includes the practice of disguise, will be outlined. Historical tales and folk stories with similar themes are examined. This thesis examines the state of mind of the writers when they composing the literary works. Furthermore, similar narrative patterns in the four selected texts under study will also be examined. Finally, the relationship between the aesthetic culture, social conduct, such as the unique culture of female scholar during the Ming and Qing Dynasties and the creative attitude of the writers will be discussed.